The hellbound heart - Barker, Clive, 1952- (Harper, 2007)
Originally published in an anthology collection called "Night Visions", this long novella was the basis for the film "Hellraiser". Considered by many Barker fans to be among his best, the story introduces Pinhead, the leader of a group of hell-spawned demons called Cenobites, as he (it?) tries to secure the soul of Uncle Frank, who foolishly thought that he could arrive at the gateway to ultimate pleasure without traveling a path of grisly torture and pain.